Characteristics of Snack Bar Substitution of Arrowroot Flour and Soy Flour as an Alternative Product for Autism Patients - Dea Saskya Eka Puji Lestari; Siswanti Siswanti; Raden Baskara Katri Anandito (Universitas Sebelas Maret (UNS), 2025)
Autism is a brain development disorder that is often found in children. Autism patients experience digestive disorders because the body is unable to digest protein, especially gluten and casein. Behavior improvement can be through Casein Free Gluten Free (CFGF) diet therapy. The CFGF diet is a biometic therapy in the form of regulating nutritional patterns by not consuming foods from cow's milk and wheat. Diet must be considered for autism patients because there are certain dietary restrictions. Snacks are one of the foods that children like. Snacks that are often found are bakery products. An alternative product development could be a snack food formulated in the form of a snack bar. Arrowroot flour has the potential to be used as a snack bar product because of its high digestibility (84.35%). Soybeans act as a binder in snack bars. Yellow sweet potato produces flakes with a sweet and crunchy taste. The research aims to determine the effect of variations in the substitution of arrowroot flour and soybean flour on chemical (moisture content and protein profile), physical (texture and color), and sensory (color, aroma, taste, texture and overall) characteristics as well as the best snack bar formula. The research used a one-factor Completely Randomized Design (CRD) with variations in the substitution of arrowroot flour and soybean flour. Based on the research results, the substitution of arrowroot flour and soybean flour significantly reduced the color of L* and increased the texture of the snack bar. The water content of the snack bar increased with the addition of soybean flour substitution. In terms of sensory characteristics, composite flour substitution significantly affected the panelists' level of preference for color, taste, texture, and overall parameters. The de garmo method calculation obtained the best formula: sample F1 (90% arrowroot flour and 10% soy flour).